RELEVANCE OF TECHNOLOGICAL INNOVATION IN THE BUSINESS COMPETITIVENESS OF MEDIUM ENTERPRISES IN HIDALGO STATE - Zorrilla, Dolores Margarita Navarrete; Gracia, Tirso Javier Hernández; Velazquez, Ma. Del Rosario García; Gracia, Jose Francisco Hernandez; Duran, Jose Gustavo Ibarra; Sevilla, Juan Alberto Carranza (European Scientific Journal, ESJ, 2014)
Currently the technology innovation is a relevant factor in both the business world, and in the research field, it has a greater importance when it is associated with variables such as competitiveness and the impact is greater because the trend of the variable of technological innovation makes in the future of business development is perceived. On the other hand competitiveness approaching to the current context, is not just the rivalry that puts an economic agent against other economic agents. It generally refers to producer’s entrepreneurs, who may compete with each other in several ways, offering higher prices, in order to obtain quality or a higher quality of the necessary factors to attract customers with lower prices, with special offers by advertising among other activities. (Ricossa, 1990).. The performance of SMEs in Mexico and in the state of Hidalgo shows lacking of development and technological innovation, and the factors used to raise their competitiveness are insufficient to solve the presented problems, showing slow progress in competitiveness and productivity. SMEs are the main support of the economy in a country, they contribute to sustainable economic development, and they generate wealth.According to the importance of technological innovation and its relevance in competitiveness, this paper aims to explore the organizational factors that in technological innovation have the medium enterprises of Hidalgo State to be competitive, to take a competitive advantage based in technological innovation.